The Role of Cognitive Fusion in Pathways to Violent Radicalization and Deradicalization - Winer, Jeffrey P. (Journal for deradicalization, 2024)
A better understanding of modifiable psychological processes that could reduce pathways to violent radicalization (VR) would greatly aid researchers, providers, policy makers, and individuals at risk for VR. Cognitive fusion, the tendency for behavior to be overly regulated and influenced by one’s thoughts and feelings, and a common intervention target within Acceptance and Commitment Therapy (ACT), may be one such fulcrum. Participants, recruited via gateway snowball sampling, were 233 young adults drawn from five communities in North America as part of Wave 4 of the Somali Youth Longitudinal Study. Utilizing moderation and mediation path analysis in MPlus, the study examined the relations between cognitive fusion, VR, and three important variables associated with VR risk: post traumatic stress symptoms, experiences of daily discrimination, and perceptions of a just government. Findings supported that higher levels of cognitive fusion were directly related to greater openness to VR. Additionally, higher levels of cognitive fusion statistically mediated the link between both daily discrimination and openness to VR as well as between post traumatic stress symptoms and openness to VR. Findings also highlighted that cognitive fusion and perceptions of a just government interacted such that openness to VR was highest in individuals who had low perceptions of a just government and had high levels of cognitive fusion. Results of this study provide preliminary evidence of the potential role of high cognitive fusion in the pathways to VR and further evidence for its potential integration as a target domain within deradicalization efforts.